MicroRNA Involved in Inflammation: Control of Eicosanoid Pathway - Ochs, Meike J.; Steinhilber, Dieter; Suess, Beatrix (Frontiers in Pharmacology, 2011)
MicroRNAs (miRNAs) have emerged as important regulators in human physiological and pathological processes. Recent investigations implicated the involvement of miRNAs in the immune system development and function and demonstrated an unexpected new regulatory level. We summarize the current knowledge about miRNA control in the development of the immune system and discuss their role in the immune and inflammatory responses with a special focus on eicosanoid signaling.